Analyzing Gender Issues And Leadership Effectiveness In Medical Education - Herry Sumual; Harol R. Lumapow; Shelty D.M Sumual (Eduvest - Journal of Universal Studies, 2024)
Medical education is an important aspect in developing a country's health system. However, there are still issues that need to be addressed, especially those related to gender and leadership within medical education. The aim of this research is to analyze gender issues and leadership effectiveness in medical education. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that gender issues in medical education reflect the imbalance that occurred when women first entered the medical field at the end of the 19th century. At that time, women focused more on the field of pediatrics because it was more accepted by societal norms at that time. As a result, history records that many early female physicians in the United States preferred to practice pediatric care and women's health. Meanwhile, in the context of leadership in medical education, the various leadership styles that are generally known are democratic, pacesetting, authoritative, affiliate, training and command styles.